PENGARUH INTENSITAS TEBANG BAYANG TERHADAP KELEMBABAN DAN DAYA DUKUNG JALAN HUTAN - Dulsalam Dulsalam; Apul Sianturi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
Road maintenance has been generally considered as a major cost component in logging cost. An investigation on the effect of shade felling intensity on the moisture content and bearing capacity of forest road was carried out at the PT Wisma Lukita forest concession area, located in South Sumatera. Shade felling at the right and left side of forest roads is considered to be a factor which affects roads quality. It is said to affect soil moisture in the forest road structure, which in turn affects its bearing capacity.In this study, the effect of a set of five shade felling intencity levels were investigated, starting at 21 percent up to 70 percent with 10 percent increments. The effect on moisture content turns out to be significant, and set of five felling intensity levels caused moisture contents to vary from 8 percent to 20 percent. The effect on bearing capacity however, is non-significant.